Effect of prompt penetration on the low latitude ASY indices - Singh, Anand K.; Sinha, Ashwini K.; Pathan, B. M.; Rajaram, R.; Rawat, Rahul (My University, 2013)
Onset of a geomagnetic substorm often intensifies the westward auroral electrojet, as well as produces asymmetric magnetic field at low-/mid-latitudes. Auroral electrojet and low latitude asymmetric indices are known to correlate well during substorms. These indices have been widely used to monitor the duration and strength of substorm activities. However, several processes, other than substorms, introduce local time asymmetry in magnetic field at low latitudes, which can substantially influence the ASY indices. Large number of substorms are observed in association with changes in the interplanetary magnetic field (IMF). It is known that sharp IMF Bz orientation changes result in penetration of interplanetary electric field (IEF) to lower latitudes, which affects the geomagnetic fields to different degree in different local times. In the present study, we demonstrate that sharp IMF Bz fluctuations during the expansion phases of substorms introduce additional asymmetry at low latitudes. The effect is clearly seen in ASYH, whereas ASYD remains almost unaltered.
Keywords: Prompt penetration; Substorm; Auroral electrojet; Asymmetry; ASY indices; Interplanetary magnetic field; Geomagnetic substorm